Application of stereotactic body radiotherapy in advanced pancreatic cancers in Australia. Issue 1 (9th November 2018) - Kim, Laurence; Nguyen, Nam; Singhal, Nimit; Phan, Vinh‐An; Iankov, Ivan; Le, Hien
Abstract: Introduction: The majority of pancreatic cancers present locally advanced and carry a high mortality rate. Treatment is challenging, with mixed data suggesting use of chemotherapy alone or in combination with radiotherapy. The use of radiotherapy has previously been limited due to lack of ability to deliver radiation to the tumour mass without causing significant toxicity to surrounding organs. Stereotactic body radiotherapy (SBRT) allows delivery of higher biologically equivalent dose in a shorter treatment duration. We sought to investigate the safety and application of this technique in our centre. Method: We enrolled 27 patients from 2015, identified as locally advanced unresectable with histologically confirmed, non‐metastatic, pancreatic adenocarcinoma. All patients had endoscopically inserted fiducial markers and where possible concurrent chemotherapy was administered. Dose schedules ranged from 25 to 42 Gy in 5 or 3 fractions. Results: With an overall median follow up of 9 months (range, 3–32.7), the median survival was 11.6 months. Of those alive at 1 year, the local control rate was 67%. Six patients had Grade 3 toxicity, and other six had Grade 2 toxicity. None had Grade 4 or above toxicity. The most common symptom recorded was fatigue. Conclusion: SBRT for locally advanced pancreatic cancer is technically complex but feasible in a high volume centre. SBRT is unique, allowing safe delivery of high radiation dose resulting in good local control and decreases treatment time making it an attractive option for patients with unresectable pancreatic cancer. Abstract : The majority of pancreatic cancers present locally advanced and carry a high mortality rate. Treatment is challenging, with mixed data. We have shown that SBRT is a unique technique, allowing safe delivery of high radiation dose resulting in good local control and decreases treatment time making it an attractive option for patients with unresectable pancreatic cancer.